PENGARUH PIUTANG TAK TERTAGIH TERHADAP ARUS KAS PADA PT SINAR REZEKI MAS MAKMUR - Maya Josefa Hutapea; Muhammad Reza Septriawan (Worksheet : Jurnal Akuntansi, 2022)
Cash flow is a financial statement that contains the effect of cash from operating activities, investment transaction activities and financing/funding transaction activities as well as the net increase or decrease in cash of a company for a period. Uncollectible accounts are one of the factors that can affect a company's operating cash flow among many other factors. The formulation of the problem in this study is whether bad debts affect cash flow and how much influence bad debts have on cash flow at PT. Sinar Rezekimas Prosperous. The purpose of the study was to test and analyze the effect of Uncollectible Receivables on Cash Flows at PT. Sinar Rezekimas Prosperous Period. The data analysis technique used is simple linear regression analysis, t test, and determination test where data processing uses SPSS version 22 program. This research produces a simple linear regression equation, namely: Y = 1.67155 - 0.118X. The results of the t-test obtained that bad debts have a significant effect on cash flow at PT. Sinar Rezekimas Makmur Medan. The coefficient of determination is 0.134, which indicates that the bad debts variable is able to explain the cash flow of 13.4%, while the remaining 86.6% is explained by other variables not examined in this study, such as accounts receivable turnover, unpaid debts and others. The company is advised to tighten credit policies, paying attention to matters relating to collection of receivables, such as overdue problems and fines for late payments. Intensely and politely remind customers of the receivables they have. Impose a fine on the customer so that the customer pays before the due date. Perform billing continuously in a polite manner and do not disturb customers.